Distribution of Hand Sanitizers and Disinfectants as Steps to Anticipate Covid-19 Transmission in Sidoarjo, Indonesia - Ersalina Nidianti; Wieke Sri Wulan (Indonesian Journal of Cultural and Community Development, 2022)
The spread of Corona Virus Disease-19 (COVID-19) in Indonesia continues to increase from time to time. East Java with the highest number of positive COVID-19 cases compared to other provinces in Indonesia. Sidoarjo is the second largest region after Surabaya in terms of positive cases of COVID-19. WHO argues that COVID-19 can spread from human to human through saliva, mucus/phlegm that comes out of the nose of a person who confirm cases with COVID-19. Efforts to maintain health from the spread of the corona virus are to maintain hand hygiene because hands often mediate the entry of microbes into the body. Wash your hands regularly using soap/hand sanitizer as an effort to prevent the spread of COVID-19. Hand sanitizers are an option because they are practical, easy to carry, and are able to inhibit the growth of bacteria/viruses. Therefore, our community service team consisting of lecturers and students of the Health Analyst-UNUSA, moved to distribute hand sanitizers (washing hands without rinsing water) and disinfectants that effectively kill bacteria/viruses. The distribution of hand sanitizers and disinfectants is given to traffic crossers in the Sidoarjo Regency area, because they have to keep working to control traffic for a relatively long time and the risk of contracting COVID-19 is relatively high. Distribution of hand sanitizers and disinfectants as a measure to anticipate the transmission and spread of COVID-19 as well as preparation for the new normal era of COVID-19 in the Sidoarjo Regency area.